Lifecycle Patterns in the Socioeconomic Gradient of Risk Preferences - Stefanie Schurer (Institute for the Study of Labor (IZA), 2015)
Who is most likely to change their risk preferences over the lifecourse? Using German nationally representative survey data and methods to separate age from cohort effects, we estimate the lifecycle patterns in the socioeconomic gradient of self-reported risk preferences. Tolerance to risk drops by 0.5 SD across all groups from late adolescence to age 40. From mid to old age, risk tolerance continues to drop for the most disadvantaged, while it stabilizes for all other groups. By age 65, the socioeconomic gradient reaches a maximum of 0.5 SD. Extreme risk aversion among the elderly poor has important policy implications.
Keywords: D81; D01; D63; 330; risk preferences; socioeconomic inequalities; life-course analysis; cohort effects; SOEP